Improvement of Short-Circuit Tolerance of Garnet Type Solid Electrolyte Li6.4La3Zr1.4Ta0.6O12 by Li2WO4 and Al2O3 Sintering Aids and La Deficiency - Yuya KONO; Yuta MASUO; Kento OBINATA; Takayuki DOI; Masakazu HARUTA; Hitoshi ONODERA; Shuhei YOSHIDA; Minoru INABA (Electrochemistry)
Garnet-type Li6.4La3Zr1.4Ta0.6O12 (LLZT) is one of the most promising solid electrolytes for all solid-state batteries due to its relatively high Li-ion conductivity and electrochemical stability against Li metal anode. However, the presence of pores and voids in the electrolyte causes short circuit due to lithium dendrites growth. In the present study, the effects of Li2WO4 (LWO) and Al2O3 sintering aids on the densification of LLZT were investigated to decrease the pores and voids and thereby to improve the tolerance for Li dendrite growth. Both sintering aids were effective for improving the densification; however, their effects were totally different. While 2 wt% Al2O3 significantly enhanced the grain growth, 4 wt% LWO gave smaller grains of uniform size distribution (3–5 µm). Simultaneous addition of 4 wt% LWO and 2 wt% Al2O3 gave relatively larger grains (5–20 µm) with very few voids, and a very high relative density of 99.3 % was obtained. The critical current density (CCD) was improved from 0.2 to 0.4 mA cm−2. Reducing the amount of lanthanum in LLZT led to the formation of lithium zirconate as a self-forming sintering aid and achieved a higher relative density (99.7 %) for La-deficient (6 %) LLZT with 4 wt% LWO and 2 wt% Al2O3. The CCD was further improved to 0.6 mA cm−2.